Acute arterial stiffness responses to on-ball balance exercises in young and middle-aged adults: Role of posture and cumulative effects - Chen, Wei; Miao, Gaofan; Xv, Yanfei; Zhou, Zhixiong; Zhu, Weili (Frontiers in Physiology, 2023)
Objective: To examine the acute arterial stiffness changes after maintaining one bout of balance on Swiss ball using different postures in young and middle-aged adults, and to evaluate the cumulative exposure effects on arterial stiffness after multiple exercise bouts in middle-aged adults. Methods: Using crossover design, we first enrolled 22 young adults (24.0 ± 1.1 years) and randomized them to non-exercise control (CON), on-ball balance exercise trial lasting 1×5 min in kneeling posture (K1) and sitting posture (S1). In a following crossover experiment, 19 middle-aged adults (53.0 ± 4.7 years) were randomized to non-exercise control (CON), on-ball balance exercise trial lasting 1×5 min in kneeling posture (K1) and in sitting posture (S1), and on-ball balance exercise trial lasting 2×5 min in kneeling posture (K2) and in sitting posture (S2). Cardio-ankle vascular index (CAVI), an indicator of systemic arterial stiffness, was measured at baseline (BL), immediately after (0 min), and every 10 min after exercise. CAVI changes from BL in the same trial (⊿CAVI) were used for analysis. Results: In K1 trial, ⊿CAVI decreased significantly at 0 min (P < 0.05) in both young and middle-aged adults; however in S1 trial, ⊿CAVI at 0 min increased significantly in young adults (P < 0.05), with ⊿CAVI tending to increase in middle-aged adults. Bonferroni post-test revealed that at 0 min, ⊿CAVI of K1 in both young and middle-aged adults, and ⊿CAVI of S1 in young adults differed significantly from that of CON (P < 0.05). In middle-aged adults, ⊿CAVI decreased significantly at 10 min compared to BL in K2 trial (P < 0.05), and increased at 0 min compared to BL in S2 trial (P < 0.05); however, difference compared to CON was not significant. Conclusions: Single on-ball balance bout in kneeling posture improved arterial stiffness transiently in both young and middle-aged adults; however, sitting posture elicited opposite changes, and this happened only in young adults. Multiple balance bouts resulted in no significant change in arterial stiffness in middle-aged adults.